Linking TIMSS and NAEP assessments to evaluate international trends in achievement - Hwanggyu Lim; Stephen G. Sireci (Arizona State University, 2017)
The Trends in International Mathematics and Science Study (TIMSS) makes it possible to compare the performance of students in the US in Mathematics and Science to the performance of students in other countries. TIMSS uses four international benchmarks for describing student achievement: Low, Intermediate, High, and Advanced. In this study, we linked the eighth-grade Math TIMSS and NAEP scales using equipercentile equating to (a) help better interpret U.S. eighth-grade students' performance on TIMSS, and (b) investigate the progress of eighth-grade U.S. students over time relative to the progress of students in other countries. Results indicated that relative to other countries, U.S. eighth-grade students increased with respect to the "At or Above Basic" NAEP Achievement level, but that other countries saw larger improvements in the higher achievement level categories, relative to the US. This finding may reflect the emphasis of No Child Left Behind on raising lower achievement to "proficient." However, with respect to "Advanced" mathematics achievement, eighth-grade U.S. students showed less improvement than students in other countries.